Mengukur Tingkat Kepuasan Pelayanan Gizi Pada Pasien Rawat Inap Melalui Rasa Makanan - AJIB JAYADI (Universitas Mitra Indonesia, 2020)
Quality hospital services will provide satisfaction to patients and are the starting point for building strong relationships for a long time. Patient satisfaction greatly impacts the number of hospital visits. This study aims to determine the factors related to the satisfaction level of nutrition services in inpatients. This study uses a quantitative research design. This type of research is analytic observational with cross sectional approach. The sample in this study were 84 respondents who were taken using purposive sampling method. The data wascollected using a questionnaire. Data analysis used to test the relationship between twovariables was the chi square test. The results showed that 53.6% of patients were notsatisfied with the nutritional services provided by Pringsewu Hospital in Lampung. There isa significant relationship between food aroma (p-value = 0.036 OR = 2.872), food spices(p-value = 0.011 OR = 3.538), and food tenderness (p-value = 0.020 OR = 3,429) with thesatisfaction level of nutrition services on inpatients.